THE EFFECT OF REGIONAL FUND TRANSFER ON DISPARITY INDICATOR FOR ECONOMIC DEVELOPMENT IN INDONESIA - B01111020, Dede Kurniawan (Jurnal Pembangunan dan Pemerataan, 2015)
(DBH), General Allocation Fund (DAU) and Special Allocation Fund (DAK) as independent variables, the indicators disparities in economic development in Indonesia which consist of, Population poor (Y1), Percapita Income (Y2), growth (Y3), and the Human Development Index (Y4) as the dependent variable. The sample used is data from 31 provinces in Indonesia in the period 2010-2014. The analytical method used is Pooled Least Squares.Results of the study found that DBH and DAK, positive effect but not significant poor population and economic growth, while DBH significant negative effect on the HDI while DAK positive effect but not significant to the HDI, DBH and DAK negative effect but no significant effect on earnings per capita, then DAU positive and significant impact on economic growth, income per capita and HDI, and DAU a significant negative effect on the number of poor people.Key words: DBH, DAU, DAK, Poverty, Income per Capita, Economic, Develpoment,Human Development Index